O canto dos helenos: poesia e performance - Santos, Fernando Brandão dos [UNESP] (Classica - Revista Brasileira de Estudos Classicos, 2013)
This study presents a brief reflection on the genesis of literary genres in Ancient Greece. It is intended here, in the first place, take us off this "comfort zone" when we talk about "Greek literature" in antiquity, at least from the period of Homer until the fifth century. B.C. , moment when, in fact, the writing has become stable not only in the continent but spreads out reaching the Italian peninsula and generating what we have today as the Roman alphabet. Therefore, we examine some terms that appear to be so clear for us which termed other doings, such as poetry, poem, among others. We also examine issues concerning the epic, lyrical and dramatic poetry.

O presente estudo propõe uma breve reflexão sobre a gênese dos gêneros literários na Grécia Antiga. Pretendese aqui, em primeiro lugar, tirar-nos dessa “zona de conforto” quando falamos em “literatura grega” na antiguidade, pelo menos do período de Homero até o século V a. C., momento em que, de fato, a escrita consolida-se não só no continente, mas se espalha mais além, alcançando a península itálica e gerando o que hoje temos como alfabeto romano. Para tanto, examinamos alguns termos que nos parecem tão claros e que designavam outros fazeres, tais como poesia, poema, entre outros. Examinamos também questões relativas às poesias épica, lírica e dramática.
The singing of the hellenes: poetry and performance
Keywords: Genesis; Literary genders; Literature; Greek literature; Antiquity; Poetry; Song; Epic poetry; Lyric poetry; Dramatic poetry; Poesia; Canto; Performance; Helenos; Poesia oral; Poesia Lírica